Entry, Exit, and Investment-Specific Technical Change - Samaniego, Roberto M (American Economic Review, 2010)
Using European data, this paper finds that (i) industry entry and exit rates are positively related to industry rates of investment-specific technical change (ISTC); and (ii) the sensitivity of industry entry and exit rates to cross-country differences in entry costs depends on industry rates of ISTC. The paper constructs a general equilibrium model in which the rate of ISTC varies across industries and new investment-specific technologies can be introduced by entrants or by incumbents. In the calibrated model, equilibrium behavior is consistent with stylized facts (i) and (ii), provided the cost of technology adoption is increasing in the rate of ISTC. (JEL G31, L11, O31, O33)